The Effect of Locus of Control, Work Motivation and Work Discipline on Job Satisfaction of Prof. Dr. Rd Kandou Manado - Rini Novita Hamdani; David Paul Elia Saerang; Rudy Steven Wenas (Research Parks Publishers, 2022)
Hospital administration is an activity of planning, supervising, organizing, directing, coordinating and evaluating in the organization of hospital activities for health purposes. The position of hospital administration employees is very important because it is related to internal conditions in the hospital and is also related to services to the community. Every employee faces different conditions in his work and sometimes it is not as expected. This discrepancy affects the level of employee job satisfaction. This study wanted to determine the effect of locus of control, work motivation and work discipline on employee satisfaction at the Prof. Central General Hospital. RD Kandou Manado. The study used a survey approach to 88 employees who became the research sample. The results showed that (1) there was a positive and insignificant effect of locus of control on employee job satisfaction, (2) there was a positive and significant influence of work motivation on employee job satisfaction, (3) there was a positive and significant influence of work discipline on job satisfaction, and (4) Simultaneously there is a significant influence of locus of control, work motivation and work discipline on employee job satisfaction at the Prof. Central General Hospital. Dr. RD Kandou Manado. and (4) simultaneously there is a significant influence of locus of control, work motivation and work discipline on job satisfaction of employees at the Prof. Central General Hospital. Dr. RD Kandou Manado. and (4) simultaneously there is a significant influence of locus of control, work motivation and work discipline on job satisfaction of employees at the Prof. Central General Hospital. Dr. RD Kandou Manado.